Pararhodobacter marinus sp. nov., a bacterium isolated from marine sediment in the East China Sea and emended description of the genus Pararhodobacter. Issue 10 (6th August 2019) - Zhang, Weiyan; Chen, Can; Yuan, Ye; Su, Dengquan; Ding, Lijian; Epstein, Slava S.; He, Shan
Abstract : A Gram-negative, rod-shaped, non-motile and strictly aerobic bacterium, designated ZQ420 T, was isolated from marine sediment sampled on Zhoushan Island located in the East China Sea. Strain ZQ420 T was able to grow at 10–45 °C, 0–12.0 % (w/v) NaCl and pH 5.5–9.0. Catalase and oxidase activities, nitrate reduction, H2 S production, hydrolysis of starch, casein, Tween 20, 40 and 80 were positive. Indole, methyl red, Voges–Proskauer test, hydrolysis of gelatin and Tween 60 were negative. The major cellular fatty acids were C18 : 1 ω 7 c, C16 : 0 and 11-methyl C18 : 1 ω7 c . Ubiquinone-10 (Q-10) was the only detected respiratory quinone. The polar lipids consisted of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, three unidentified phospholipids, three unidentified glycolipids, two unidentified aminolipid and two unidentified lipids. The DNA G+C content was 64.8 mol%. According to 16S rRNA gene sequence similarities, strain ZQ420 T shared 97.9, 96.3 and 96.3 % similarities to the following species with validated names Pararhodobacter aggregans D1-19 T, Pseudo rhodobacter psychrotolerans PAMC27389 T and Pseudo rhodobacter collinsensis 4-T-34 T, respectively. While sharing lower sequence similarities (<96.0 %) to other type species. Phylogenetic analyses showed that strain ZQ420 T and P. aggregans D1-19 T formed an independent cluster in the phylogenetic trees. The average nucleotide identity value between strain ZQ420 T and P. aggregans D1-19 T was 79.1 %. The in silico DNA–DNA hybridization analysis revealed that strain ZQ420 T shared 21.5 % DNA relatedness with P. aggregans D1-19 T . On the basis of its phenotypic, chemotaxonomic and genotypic characteristics, strain ZQ420 T is considered to represent a novel species in the genus Pararhodobacter, for which the name Pararhodobacter marinus sp. nov. is proposed. The type strain is ZQ420 T (=KCTC 62579 T =MCCC 1K03530 T ).